Visual impairment and blindness in the Xingu Indigenous Park - Brazil - Arthur Gustavo Fernandes; Monica Alves; Roberta Andrade e Nascimento; Natalia Yumi Valdrighi; Rafael Cunha de Almeida; Celso Takashi Nakano (BMC, 2021)
Abstract Background Most estimates of visual impairment and blindness worldwide do not include data from specific minority groups as indigenous populations. We aimed to evaluate frequencies and causes of visual impairment and blindness in a large population sample from the Xingu Indigenous Park. Methods Cross-sectional study performed at Xingu Indigenous Park, Brazil, from 2016 to 2017. Residents from 16 selected villages were invited to participate and underwent a detailed ocular examination, including uncorrected (UVA) and best-corrected visual acuity (BCVA). The main cause of UVA < 20/32 per eye was determined. Results A total of 2,099 individuals were evaluated. Overall, the frequency of visual impairment and blindness was 10.00% (95% CI: 8.72-11.29%) when considering UVA, decreasing to 7.15% (95% CI: 6.04-8.25%) when considering BCVA. For each increasing year on age, the risk  of being in the visually impaired or blind category increased by 9% (p < 0.001). Cataracts (39.1%) and uncorrected refractive errors (29.1%) were the most frequent causes of visual impairment and blindness in this population. The main causes among those aged 45 years and more were cataracts (54.5%) while refractive errors were the main cause in adults aged 18 to 45 years (50.0%) and children up to 18 years old (37.1%). Conclusions A higher frequency of visual impairment and blindness was observed in the indigenous population when compared to worldwide estimates with most of the causes being preventable and/or treatable. Blindness prevention programs should focus on accessibility to eye exam, cataract surgeries and eyeglass distribution.